2019
DOI: 10.1002/hfm.20798
|View full text |Cite
|
Sign up to set email alerts
|

Driver glance behaviors and scanning patterns: Applying static and dynamic glance measures to the analysis of curve driving with secondary tasks

Abstract: Performing secondary tasks (or non‐driving‐related tasks) while driving on curved roads may be risky and unsafe. The purpose of this study was to explore whether driving safety in situations involving curved roads and secondary tasks can be evaluated using multiple measures of eye movement. We adopted Markov‐based transition algorithms (i.e., transition/stationary probabilities, entropy) to quantify drivers’ dynamic eye movement patterns, in addition to typical static visual measures, such as frequency and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, for differently abled or other individuals who cannot conveniently use these devices, modern human–computer interaction systems are not user‐friendly. Recently, eye‐related data have been widely used in interface assessment (Goldberg & Kotval, 1999), ergonomic analysis of behaviors (Jeong et al, 2019; Niu et al, 2020; Yang et al, 2018), and cognitive load assessment (Ahlstrom & Friedman‐Berg, 2006). Further, through the processing and calculation of eye‐tracking data, eye movement has gradually been used as a new interactive method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for differently abled or other individuals who cannot conveniently use these devices, modern human–computer interaction systems are not user‐friendly. Recently, eye‐related data have been widely used in interface assessment (Goldberg & Kotval, 1999), ergonomic analysis of behaviors (Jeong et al, 2019; Niu et al, 2020; Yang et al, 2018), and cognitive load assessment (Ahlstrom & Friedman‐Berg, 2006). Further, through the processing and calculation of eye‐tracking data, eye movement has gradually been used as a new interactive method.…”
Section: Introductionmentioning
confidence: 99%
“…of behaviors (Jeong et al, 2019;Niu et al, 2020;Yang et al, 2018), and cognitive load assessment (Ahlstrom & Friedman-Berg, 2006).…”
mentioning
confidence: 99%
“…The direct eye tracking indices, which are generated based on fundamental fixation and saccade, cannot be a proxy for the driving task performance. This is because that these indices are basically simple statistics and only applicable for specific applications, so as not to behave generally and robustly as an estimator of visual scanning efficiency [7].…”
Section: Resultsmentioning
confidence: 99%
“…Fixation and saccade are classic indices for this purpose. But, direct and indirect usages of these indices (for examples, rate/duration of them and their simple combinations) are more applicable in specific application scenarios [12], than in the general efficiency definition. In addition, pupil dilation and blink rate are two widely used eye tracking indices for the study of cognition and psychology [13].…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the entropy method could achieve good classification performance in driving fatigue studies [ 25 ]. Jeong et al stated that compared with typical static measures, the Markov-based entropy method can quantify eye movement and provide a better understanding of individual switching patterns [ 26 ].…”
Section: Introductionmentioning
confidence: 99%